2007
DOI: 10.1523/jneurosci.2003-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Long-Term Potentiation Occurs within Individual Hippocampal Synapses during Learning

Abstract: Stabilization of long-term potentiation (LTP) depends on multiple signaling cascades linked to actin polymerization. We used one of these, involving phosphorylation of the regulatory protein cofilin, as a marker to test whether LTP-related changes occur in hippocampal synapses during unsupervised learning. Well handled rats were allowed to explore a compartmentalized environment for 30 min after an injection of vehicle or the NMDA receptor antagonist (Ϯ)-3-(2-carboxypiperazin-4-yl)propyl-1-phosphonic acid (CPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 44 publications
9
105
0
Order By: Relevance
“…When MMP activity is eliminated during TBP, both spine enlargement and potentiation are transient. Our results suggest that MMP-9 functions during LTP as a local, instructive extracellular signal that consolidates synaptic structural and functional modifications coordinately, ensuring persistent modifications critical for learning and memory (30,31). After TBP, there is an immediate increase in both spine size and EPSPs.…”
Section: Discussionmentioning
confidence: 74%
“…When MMP activity is eliminated during TBP, both spine enlargement and potentiation are transient. Our results suggest that MMP-9 functions during LTP as a local, instructive extracellular signal that consolidates synaptic structural and functional modifications coordinately, ensuring persistent modifications critical for learning and memory (30,31). After TBP, there is an immediate increase in both spine size and EPSPs.…”
Section: Discussionmentioning
confidence: 74%
“…There is a large amount of literature linking the hippocampus to this type of activity, and unsupervised paradigms provide multiple dimensions across which to detect behavioral differences (24). The distance traveled by 16-week-old CAG140 mice (n ϭ 19) was reduced relative to WT (Ϫ35 Ϯ 6% on test day 1; P Ͻ 0.0001, n ϭ 17, 2-tailed t test; Fig.…”
Section: Effects Of Chronic Ampakine Treatment On Behavior Of Cag140 mentioning
confidence: 95%
“…Mice were tested for 60 min over 4 consecutive days in a complex open-field environment, used previously (24), that lacked objects/compartments on day 1. On testing days 2 and 3, an enclosed dark compartment and 2 identical objects were added to the arena; one object was replaced with a novel object on testing day 4 (Fig.…”
Section: (Si Text)mentioning
confidence: 99%
“…This constitutively active protein severs developing actin filaments unless inactivated by phosphorylation, a step that is critical to the production of the cytoskeletal changes required for LTP consolidation (Chen et al 2007;Rex et al 2009). Previous studies showed that unsupervised learning in a simple open field by rats with no prior experience increases the percentage of hippocampal synapses containing relatively high levels of pCofilin within hippocampal field CA1; an NMDA receptor antagonist blocked both the synaptic changes and memory encoding (Fedulov et al 2007). Studies using other synaptic markers of LTP confirmed that simple unsupervised learning elicits the potentiation effect in the hippocampus of naive rats (Chen et al 2010a,b).…”
Section: Discussionmentioning
confidence: 99%